CD90 Marks a Mesenchymal Program in Human Thymic Epithelial Cells In Vitro and In Vivo - Sun, Shicheng; Li, Jacky Y.; Nim, Hieu T.; Piers, Adam; Ramialison, Mirana; Porrello, Enzo R.; Konstantinov, Igor E.; Elefanty, Andrew G.; Stanley, Edouard G. (Frontiers in Immunology, 2022)
Thymic epithelium is critical for the structural integrity of the thymus and for T cell development. Within the fully formed thymus, large numbers of hematopoietic cells shape the thymic epithelium into a scaffold-like structure which bears little similarity to classical epithelial layers, such as those observed in the skin, intestine or pancreas. Here, we show that human thymic epithelial cells (TECs) possess an epithelial identity that also incorporates the expression of mesenchymal cell associated genes, whose expression levels vary between medullary and cortical TECs (m/cTECs). Using pluripotent stem cell (PSC) differentiation systems, we identified a unique population of cells that co-expressed the master TEC transcription factor FOXN1, as well as the epithelial-associated marker EPCAM and the mesenchymal associated gene CD90. Using the same serum-free culture conditions, we also observed co-expression of EPCAM and CD90 on cultured TECs derived from neonatal human thymus in vitro. Single-cell RNA-sequencing revealed these cultured TECs possessed an immature mTEC phenotype and expressed epithelial and mesenchymal associated genes, such as EPCAM, CLDN4, CD90, and COL1A1. Importantly, flow cytometry and single-cell RNA-sequencing analysis further confirmed the presence of an EPCAM+CD90+ population in the CD45- fraction of neonatal human thymic stromal cells in vivo. Using the human thymus cell atlas, we found that cTECs displayed more pronounced mesenchymal characteristics than mTECs during embryonic development. Collectively, these results suggest human TECs possess a hybrid gene expression program comprising both epithelial and mesenchymal elements and provide a basis for the further exploration of thymus development from primary tissues and from the in vitro differentiation of PSCs.